Respon Konsumen Terhadap Iklan Mie Sedaap - Susanta, Susanta (Jurnal Ilmu Komunikasi, 2008)
The aims of the research are identzj5â Mie Sedaap advertising strength, customer c response strength, customer response index, and relationship between advertising strength and customer s response strength. Closed questionnaire is use to collect data froni 100 respondents. Purposive sampling technique used to determine respondent. Date tabulating is kind of descriptive analysis that is used to analysis advertising strength, customers â response strength, and custon2ers âresponse index. Rank Spearman correlation use to analysis relationship between advertising strength and customers âresponse strength. The result of descriptive analysis show that strength of Mie Sedaap achâertising lid Kanial Version is in the average category it means the respondent see the advertising very oflen but there & no special thing on the interest build. âith the hierarchy effect model, it shows the consumer respondent has goes outside aivareness, interest, desire, convict, and purchase level. Most of the respondents do the purchase, while some respondent dzdn purchase just because they didn ât get convicted about what the advertising claim and did,, â1 get interest whit that. Mie Sedaap advertising can be categorized success because most of the people buy the goods. But if we look to the strength of the advertising which created only iveak responses, there c no guarantee they will buy again in the future or continuing the purchase. In the other hand,for those who haven bought the product, still very small possibility to buy. It is because the weak support from the advertising. The result of correlation analysis also shows relations between strength of the advertising and strength of consumer response is sign /Icant on level a = 0.05 If the company wants to get the goal offrom tiie advertising, they have to repair the advertising so it cciii improve the awareness, interest, desire, conviction and purchase level. Key word. advertising strength, customer âresponse strength, customer âresponse index